Enhancing carrot (Daucus carota var. sativa Hoffm.) plant productivity with combined rhizosphere microbial consortium - Zhu, Liping; Zhang, Peiqiang; Ma, Shunan; Yu, Quan; Wang, Haibing; Liu, Yuexuan; Yang, Song; Chen, Yanling (Frontiers in Microbiology, 2024)
BackgroundPlant growth-promoting rhizobacteria (PGPR) are an integral part of agricultural practices due to their roles in promoting plant growth, improving soil conditions, and suppressing diseases. However, researches on the PGPR in the rhizosphere of carrots, an important vegetable crop, is relative limited. Therefore, this study aimed to isolate and characterize PGPR strains from the rhizosphere soil of greenhouse-grown carrots, with a focus on their potential to stimulate carrot growth.MethodsThrough a screening process, 12 high-efficiency phosphorus-solubilizing bacteria, one nitrogen-fixing strain, and two potassium-solubilizing strains were screened. Prominent among these were Bacillus firmus MN3 for nitrogen fixation ability, Acinetobacter pittii MP41 for phosphate solubilization, and Bacillus subtilis PK9 for potassium-solubilization. These strains were used to formulate a combined microbial consortium, N3P41K9, for inoculation and further analysis.ResultsThe application of N3P41K9, significantly enhanced carrot growth, with an increase in plant height by 17.1% and root length by 54.5% in a pot experiment, compared to the control group. This treatment also elevated alkaline-hydrolyzable nitrogen levels by 72.4%, available phosphorus by 48.2%, and available potassium by 23.7%. Subsequent field trials confirmed the efficacy of N3P41K9, with a notable 12.5% increase in carrot yields. The N3P41K9 treatment had a minimal disturbance on soil bacterial diversity and abundance, but significantly increased the prevalence of beneficial genera such as Gemmatimonas and Nitrospira. Genus-level redundancy analysis indicated that the pH and alkali-hydrolyzable nitrogen content were pivotal in shaping the bacterial community composition.DiscussionThe findings of this study highlight the feasibility of combined microbial consortium in promoting carrot growth, increasing yield, and enriching the root environment with beneficial microbes. Furthermore, these results suggest the potential of the N3P41K9 consortium for soil amelioration, offering a promising strategy for sustainable agricultural practices.